2003
DOI: 10.1111/j.1728-4465.2003.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Young Malians' Reluctance to Use Hormonal Contraceptives

Abstract: During a qualitative evaluation of three peer-education programs in urban Mali, young people stated that they were wary of using either the pill or injectable contraceptives because they believed that these methods would make them sterile. Unmarried women's contraceptive decisionmaking was not primarily driven by a current need to limit fertility, but rather by a future need to maximize it in order to gain status through childbearing in their marital households. Further interviews explored notions of conceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 31 publications
7
94
1
2
Order By: Relevance
“…2013; Williamson et al. 2009; Castle 2003). Such concerns are likely to be more of a deterrent to use and selection of methods among younger women wishing to space or postpone childbearing than among those wanting to limit family size.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Williamson et al. 2009; Castle 2003). Such concerns are likely to be more of a deterrent to use and selection of methods among younger women wishing to space or postpone childbearing than among those wanting to limit family size.…”
Section: Discussionmentioning
confidence: 99%
“…12 Secondly, non-barrier contraception is unpopular because of fears of side effects and unwarranted but common fears that future childbearing might be jeopardised by use of hormonal methods. 19,20 Moreover, condom use can be justified in terms of pregnancy avoidance even in relationships where fear of HIV infection is a major consideration. It needs no research to assert that negotiation of condoms for family planning is much easier than negotiation to avoid disease because it carries no imputation of distrust.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to a study in Mali, many women feared that the pill and the injectable could cause permanent infertility. 9 A qualitative study in Kenya among sexually active women aged 15–25 demonstrated that many women had misconceptions about the side effects of modern contraceptives (e.g., that they cause infertility or can harm a woman's uterus), but few had experienced or knew someone who had experienced an actual side effect (e.g., weight gain). 10 In another qualitative study in Kenya among reproductive-age women, one respondent reported that the pill “can accumulate into a life-threatening mass in the stomach, can cause blood to flow out of the nose and mouth, and can cause delivery of children with two heads and no skin.” 11 Myths and misconceptions about methods can spread through informal communication via social networks and lead to continued negative perceptions.…”
mentioning
confidence: 99%